The Effectiveness of Using Zoom Meeting in Learning Phonology Courses for Students of the Indonesian Language and Literature Education Study Program, Wiralodra University - Amanatul Maula; Lina Sri Melati; Didik Himmawan (Manajia: Journal of Education and Management, 2025)
This study raises the title The Effectiveness of Using Zoom Meetings in Learning Phonology for Indonesian Language and Literature Education Study Program students at Wiralodra University. This study aims to determine the effectiveness of using zoom meetings in learning phonology courses. The discussion in this study is about phonology courses, zoom meeting applications, the use of features in zoom meetings, the advantages and disadvantages of zoom meetings, the role of zoom meetings as a distance learning medium and the effectiveness of zoom meeting media in phonological learning. The results of this study, the Zoom Meeting and Google Meeting applications are applications that can be used as learning media that can contain interactions between lecturers and students in learning where these are suitable for use in phonology courses. This study used descriptive qualitative method.